Caregivers' role in using a personal electronic health record: a qualitative study of cancer patients and caregivers in Germany - Weis, Aline; Pohlmann, Sabrina; Poss-Doering, Regina; Strauss, Beate; Ullrich, Charlotte; Hofmann, Helene; Ose, Dominik; Winkler, Eva C.; Szecsenyi, Joachim; Wensing, Michel (BMC medical informatics and decision making, 2020)
Background Particularly in the context of severe diseases like cancer, many patients wish to include caregivers in the planning of treatment and care. Many caregivers like to be involved but feel insufficiently enabled. This study aimed at providing insight into patients’ and caregivers’ perspectives on caregivers’ roles in managing the patient portal of an electronic personal health record (PHR). Methods A descriptive qualitative study was conducted comprising two study phases: (1) Usability tests and interviews with patients with cancer and caregivers (2) additional patient interviews after a 3-month-pilot-testing of the PHR. For both study parts, a convenience sample was selected, focusing on current state of health and therapy process and basic willingness to participate and ending up with a mixed sample as well as saturation of data. All interviews were audio-recorded, pseudonymized, transcribed verbatim and qualitatively analyzed. Results Two main categories emerged from qualitative data: ‘Caregivers’ role’ and ‘Graduation of access rights’ – consisting of four subcategories each. The interviewed patients ( n = 22) and caregivers ( n = 9) felt that the involvement of caregivers is central to foster the acceptance of a PHR for cancer patients. However, their role varied from providing technical support to representing patients, e.g. if the patient’s state of health made this necessary. Heterogeneous opinions emerged regarding the question whether caregivers should receive full or graduated access on a patient’s PHR. Conclusions In order to support the patient and to participate in the care process, caregivers need up-to-date information on the patient’s health and treatment. Nevertheless, some patients do not want to share all medical data with caregivers, which might strain the patient-caregiver relationship. This needs to be considered in development and implementation of personal health records. Generally, in the debate on patient portals of a personal health record, paying attention to the role of caregivers is essential. By appreciating the important relationship between patients and caregivers right from the beginning, implementation, of a PHR would be enhanced. Trial registration ISRCTN85224823 . Date of registration: 23/12/2015 (retrospectively registered).